2021
DOI: 10.1038/s42255-021-00483-8
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic roots of senescence: mechanisms and opportunities for intervention

Abstract: Cellular senescence entails a permanent proliferative arrest, coupled to multiple phenotypic changes. Among these changes is the release of numerous biologically active molecules collectively known as the senescence-associated secretory phenotype, or SASP. A growing body of literature indicates that both senescence and the SASP are sensitive to cellular and organismal metabolic states, which in turn can drive phenotypes associated with metabolic dysfunction. Here, we review the current literature linking senes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
268
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(275 citation statements)
references
References 217 publications
7
268
0
Order By: Relevance
“…In age-related diseases, cell senescence has been shown to be modulated by both redox and metabolic shifts [ 55 , 56 ]. Here, we also revealed that SIRT3-inhibited NSC senescence really depends on SIRT3’s role in mediating both LCAD activation and oxidative protection.…”
Section: Discussionmentioning
confidence: 99%
“…In age-related diseases, cell senescence has been shown to be modulated by both redox and metabolic shifts [ 55 , 56 ]. Here, we also revealed that SIRT3-inhibited NSC senescence really depends on SIRT3’s role in mediating both LCAD activation and oxidative protection.…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic stress acts as both a driver and consequence of cellular senescence. Mitochondrial dysfunction such as a disrupted nicotinamide adenine dinucleotide (NAD + )/ nicotinamide adenine dinucleotide hydride (NADH) cytosolic ratio can result in adenosine triphosphate (ATP) depletion and ultimately cell cycle arrest [29]. Damage caused by mitochondrial ROS such as the release of chromatin fragments may also drive senescence and promote SASP factors.…”
Section: Inducers and Metabolic Activity Of Senescent Cellsmentioning
confidence: 99%
“…Damage caused by mitochondrial ROS such as the release of chromatin fragments may also drive senescence and promote SASP factors. A disrupted NAD + metabolism can activate the nuclear factor kappa-light-chain-enhancer of the activated B cells (NF)-κB pathway which has a casual role in promoting senescence and the SASP [29,30]. Moreover, the SASP activates CD38 + macrophages which further depletes NAD + , as seen in senescence-induced dermal fibroblasts and aged mice models.…”
Section: Inducers and Metabolic Activity Of Senescent Cellsmentioning
confidence: 99%
See 2 more Smart Citations